Analisis Kesalahan Penggunaan Huruf Kapital Pada Koran Tribun Sumsel - Husna H; Puspa Indah Utami; Dessy Wardiah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The problem in this study is the misuse of capital letters found in the South Sumatra Tribun newspaper. This study aims to determine the error in the use of capital letters in the South Sumatra Tribun newspaper. This research was conducted using qualitative descriptive methods. The data collection process used in this study was by observation technique. The source of data used in this study is the Saturday, October 21, 2023 edition of the South Sumatra Tribun newspaper. The result of this study is that in the South Sumatra Tribun newspaper there are still errors in writing capital letters in the middle of sentences, the use of capital letters at the beginning of the words of people's names, country names, institution names, and errors in the use of capital letters in the name of the organization.